Hubungan Hipertensi dengan Penyakit Jantung Koroner (PJK): Tinjauan Pustaka - Avis Meyvika Worocahyo; Intanri Kurniati; Putri Damayanti; Susianti Susianti (Medula, 2025)
Coronary Artery Disease (CAD) remains a leading cause of morbidity and mortality worldwide, including in Indonesia, where its prevalence continues to increase alongside the high burden of hypertension. Hypertension is recognized as a major cardiovascular risk factor due to its role in accelerating atherosclerosis and inducing structural and functional alterations in the cardiovascular system. This study aims to analyze the relationship between hypertension and CAD through a literature review of national studies conducted in Indonesia. Relevant articles were obtained from online scientific databases and selected based on predefined inclusion criteria, focusing on studies that examined hypertension as a risk factor for CAD. The findings consistently demonstrate a statistically significant association between hypertension and CAD incidence, with most studies reporting p-values < 0.05. Individuals with hypertension have more than a twofold increased risk of developing CAD compared to normotensive individuals. From a pathophysiological perspective, chronic hypertension contributes to endothelial dysfunction, hemodynamic disturbances, activation of the renin–angiotensin–aldosterone system, and cardiac remodeling, all of which accelerate coronary atherosclerosis and increase the risk of myocardial ischemia. In addition, prolonged elevated blood pressure promotes plaque formation and instability, which may lead to acute coronary events. In conclusion, hypertension plays a critical role in the development of CAD. Early detection, optimal blood pressure control, and lifestyle modification are essential strategies to reduce cardiovascular risk and lower the overall burden of coronary artery disease in Indonesia.